1996
DOI: 10.1046/j.1471-4159.1996.67020868.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Protein Kinase C in γ‐Aminobutyric Acid Release from Xenopus Oocytes Injected with Rat Brain mRNA

Abstract: Involvement of protein kinase C (PKC) in the release of y-aminobutyric acid (GABA) was examined in Xenopus IaevIs oocytes injected with mRNA from rat cerebellum, as compared with findings in slices of rat cerebellum. The mRNA-injected 00cytes preloaded with [ 3H}GABA showed spontaneous release of [3H]GABA,~-0.5% of GABA content per 1 mm. Stimulation with either Ca2 ionophore (A231 87) or a high~concentration increased the release of [3H]GABA from slices of rat deep cerebellar nucleus and mRNA-injected oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…results in longer duration of 4-APinduced repetitive action potentials, Ca2" entry (built up of the bulk [Ca2"] 1), and glutamate exocytosis (Tibbs et al, 1989(Tibbs et al, , 1996. Such a mechanism could also be effective for slow CCK-8 and fast GABA exocytosis, in contrast with other studies using KC1 depolarization (Allard and Beinfeld, 1988;Shuntoh et al, 1989;Kan et al, 1996). Although the locus of action of PKC may be quite similar for stimulating both CCK-8 and GABA exocytosis, the two transmitters showed a difference in their sensitivity for /3-PDBu (Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…results in longer duration of 4-APinduced repetitive action potentials, Ca2" entry (built up of the bulk [Ca2"] 1), and glutamate exocytosis (Tibbs et al, 1989(Tibbs et al, , 1996. Such a mechanism could also be effective for slow CCK-8 and fast GABA exocytosis, in contrast with other studies using KC1 depolarization (Allard and Beinfeld, 1988;Shuntoh et al, 1989;Kan et al, 1996). Although the locus of action of PKC may be quite similar for stimulating both CCK-8 and GABA exocytosis, the two transmitters showed a difference in their sensitivity for /3-PDBu (Fig.…”
Section: Discussionmentioning
confidence: 98%
“…One of the enzymes involved in modulating the release of SCCV containing the transmitter glutamate is protein kinase C (PKC), although the locus of its action is still controversial (Nichols et al, 1987;Barrie et al, 1991;Terrian et al, 1991;Sanchez-Prieto et al, 1994). It was observed that PKC also stimulates vesicular GABA release in several cellular preparations (Shuntoh et al, 1989;Kan et al, 1996), but it has not yet been shown in isolated synaptosomes. PKC is a Ca2t and phospholipid-dependent enzyme Cholecystokinin (CCK)-like immunoreactivity (CCK-LI) has been detected throughout the CNS but is particularly abundant in the neocortex and the hippocampus (Innis et al, 1979).…”
mentioning
confidence: 99%